2012
DOI: 10.1016/j.mayocp.2012.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of the Metabolic Syndrome and Multiple Traditional Cardiovascular Risk Factors on Vascular Function

Abstract: Objective: To assess the effect of the metabolic syndrome (MetS) on endothelial function and compare these findings to those in individuals with a similar burden of traditional cardiovascular (CV) risk factors (Ն3) without MetS. Patients and Methods: Both MetS and multiple CV risk factors were identified from 1103 individuals who underwent the evaluation of endothelial function at the Mayo Clinic, in Rochester, Minnesota, from July 1, 2000, through July 31, 2011. Endothelial function was measured using digital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 56 publications
5
14
0
Order By: Relevance
“…We found a statistically independent association between MetS and coronary microvascular endothelial dysfunction particularly in relation to increasing MetS risk factor burden. Our results are in agreement with findings in the peripheral circulation where endothelial responses to pressure alterations to finger cuff (using digital arterial tonometry), to increased flow in the brachial artery and to ACH in the femoral microcirculation were impaired in subjects with MetS [16,19,20]. Although we also observed increasing epicardial endothelial dysfunction with exposure to MetS components, this relationship did not persist after adjustment for the presence of CAD.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found a statistically independent association between MetS and coronary microvascular endothelial dysfunction particularly in relation to increasing MetS risk factor burden. Our results are in agreement with findings in the peripheral circulation where endothelial responses to pressure alterations to finger cuff (using digital arterial tonometry), to increased flow in the brachial artery and to ACH in the femoral microcirculation were impaired in subjects with MetS [16,19,20]. Although we also observed increasing epicardial endothelial dysfunction with exposure to MetS components, this relationship did not persist after adjustment for the presence of CAD.…”
Section: Discussionsupporting
confidence: 91%
“…Although a previous study found a correlation between CRP levels and forearm vascular endothelial function, adjustment for obesity or MetS was not performed [52]. Others have confirmed our observations [16,22,53]. Furthermore, despite higher CRP levels in obese subjects and in those with MetS as previously reported, the association between endothelial dysfunction and MetS was not affected by further adjustment for CRP levels.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…infusion of endothelium-dependent agonists) challenge. 38,39 However, this blunted vasodilator response may be dependent on the length of exposure to the altered metabolic state, as younger adults with MetS demonstrated preserved endothelium-dependent vasodilation of the microvasculature. 40 In addition, there is enhanced vasoconstriction depicted by increased circulating endothelin-1 in MetS, 41 and increased vasoconstrictor tone after endothelin-1 infusion in diabetic patients with MetS.…”
Section: Microvascular Functionmentioning
confidence: 99%
“…8 Besides patients with low cardiovascular risk, we have recently shown that higher leukocyte count is associated with endothelial dysfunction in patients with high cardiovascular risk. 9 Therefore, we are also looking forward to future studies on the effect of antiinflammatory treatment and reduction in leukocyte count on primary prevention.…”
mentioning
confidence: 99%